Mediasi Emosi Postif Pelanggan: Pengaruh Paket Bonus Terhadap Pembelian Impulsif - Anita Nurul Cahyani; Agus Suyatno; Esti Dwi Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Nowadays, the development of the retail business in Indonesia has been increasingly rapid. This is marked by the presence of traditional markets which over time have been replaced by the emergence of modern markets with various types, giving rise to various types of retail shopping centers with different shapes and sizes. This study aims to analyze the mediating role of positive emotions between discounts and bonus packages on impulse purchases at Laris Toserba Sukoharjo. The population in this study were all visitors or consumers of Laris Toserba Sukoharjo and the number of samples used in this study were 97 respondents. The variables used in this study are price discounts, bonus packages, impulse purchases and positive emotions. The data used in this study are primary data. The data collection method used is a questionnaire. The data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS) and uses SmartPLS 4.0. The results of this study indicate that, bonus packages have a positive and significant effect on impulse purchases, bonus packages have a positive and significant effect on positive emotions, positive emotions have a positive and significant effect on impulse purchases and mediation of positive emotions has a positive and significant effect on bonus packages on impulse purchases.